Oblique facial cleft - Chi Adam, Khairul Bariah; Hariri, Firdaus; Abdul Rahman, Zainal Ariff (2015)
Introduction: Oblique facial clefts are an extremely rare disorder, accounting for only 0.24% of facial clefts.The condition causes pronounced facial deformity which can lead to major cosmetic and functional problems. Due to its nature of complexity, it becomes one of the reconstructive challenges which require careful planning and multiple surgeries throughout life.In this case report, we would like to share our experience with orbital reconstruction by means of distraction osteogenesis in a 1 and a half-year-old girl.